THU0092 DEFINING A LEARNING CURVE FOR CLINICIANS PERFORMING ULTRASOUND-GUIDED DEFINING A LEARNING CURVE FOR CLINICIANS PERFORMING ULTRASOUND-GUIDED NEEDLE SYNOVIAL BIOPSIES: A RETROSPECTIVE ANALYSIS OF THE EXPERIENCE AT THE EXPERIMENTAL MEDICINE AND RHEUMATOLOGY, QUEEN MARY UNIVERSITY OF LONDON. (June 2019) - Nerviani, Alessandra; Humby, Frances; Ribera, Gloria Lliso; Rivellese, Felice; Kelly, Stephen; Hands, Rebecca; Pitzalis, Costantino
Abstract : Background: Despite the significantly better outcome reached by patients with Rheumatoid Arthritis following the introduction of the biologics, the absence of predictors of individual response to the available agents constitutes a huge unmet clinical need. The histological analysis of the diseased synovial tissue (ST) may represent a valuable prognostic tool. The ultrasound-guided needle synovial biopsy (US-nSB) is a safe, effective and increasingly used method to retrieve ST from both large and small joints. Therefore, assessing the 'learning curve' for clinicians training in this technique is critically important. Objectives: To retrospectively evaluate the learning curve for clinicians performing US-nSB at the Centre for Experimental Medicine and Rheumatology, Queen Mary University of London. Methods: The performance of 5 clinicians has been evaluated from their first to >20 procedures based on the training phase (Table). The standard teaching method included: US/US-guided injections; observation of US-nSB; initial procedures occurring under the strict active supervision of an expert. Results: The total number of ST fragments retrieved during the procedure did not significantly change during the learning phase (17.3 ± 3.5 from 1 st to 10 th biopsy vs 17.2 ± 3.4 if expert performer). Independently of the training phase, a significantly higher number of samples were retrieved from knees/wrists in comparison with metacarpo-, metatarso-, and proximal inter-phalangeal joints. The average weight of a ST fragment at the beginning of the learning curve was comparable with the mean weight of ST samples retrieved by expert performers (3.7±2.5mg from 1 st to 10 th biopsy vs 2.9±2.4mg if experts). ST from knees had a significantly higher mean weight, which could be explained by the more frequent use of a 14G (rather than 16G) needle. At the beginning of the learning curve, 48.2%±29.5% of the retrieved ST-samples were considered histologically 'gradable' (visible lining and/or clear sub-lining based on H&E/CD68 IHC staining); the rate of gradable ST progressively increased and remained ≈60% when >20 procedures have been performed. The duration of the US-nSB significantly decreased during the learning time (49 ± 18 min from 1 st to 10 th biopsy vs 30 ± 9 min if expert performer). No serious adverse events (AEs) such as haemarthrosis or joint infection have occurred during the learning time. The overall rate of minor AEs (e.g., minor bleeding) was not the highest at the beginning of the training. During the 1 st -10 th procedures, 18.2% of the patients reported severe pain compared to the average 8.4%. Conclusion: In this single-centre retrospective study we showed that, with an appropriate training and the presence of the initial strict supervision, performing US-nSB is safe and effective since the beginning of the learning curve. Further prospective and multi-centre studies are needed to confirm the optimal learning time and training method. References: [1] Ultrasound-guided synovial biopsy: a safe, well-tolerated and reliable technique for obtaining high-quality synovial tissue from both large and small joints in early arthritis patients. S Kelly et al. Ann Rheum Dis. 2015 Mar;74(3):611-7. [2] Patient-reported outcomes and safety in patients undergoing synovial biopsy: comparison of ultrasound-guided needle biopsy, ultrasound-guided portal and forceps and arthroscopic-guided synovial biopsy techniques in five centres across Europe. SA Just, et al. RMD Open. 2018 Oct 26;4(2):e000799. Disclosure of Interests: Alessandra Nerviani: None declared, Frances Humby: None declared, Gloria Lliso Ribera: None declared, Felice Rivellese: None declared, Stephen Kelly: None declared, Rebecca Hands: None declared, Costantino Pitzalis Grant/research support from: Celgene